Can acceptance promote life satisfaction during a work from home regime? The mediating role of work-life balance and job stress - Gugup Kismono; Widya Paramita; Gabriela B. Lintang (Cogent Business & Management, 2023)
The COVID-19 pandemic has come to an end, so organizations need to make decisions about whether to maintain the work-from-home (WFH) practice or to go back to pre-pandemic working arrangements. Statistics showed that although 56% of the employers continue to adopt WFH the rest of it called back the employees back to the office in 2023. Moreover, he literature on the benefits of WFH has produced mixed findings, and so this study evaluates the impact of employees' psychological acceptance on the life satisfaction of employees who practiced WFH due to the pandemic. A survey was administered to employees in Indonesia who worked from home and 406 valid and completed responses were returned to be analysed using Smart-PLS statistical software. This study contributes theoretically by highlighting the role of context in predicting the influence of acceptance on life satisfaction. In the WFH context, acceptance is neither directly related to life satisfaction, nor promote life satisfaction by reducing job stress. However, acceptance represents a psychological resource that help employees to improve work-life balance (WLB), as balancing WLB is one of the most relevant issues during the WFH arrangement. Several managerial implications are elaborated, mainly to ensure employees gain a mindset of acceptance through recruitment and training.
Keywords: 650; job stress; life satisfaction; pandemic era; work from home; work-life balance; Work-related acceptance